A modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery

CN123017990APending Publication Date: 2026-10-30ZHEJIANG ZHIYUAN NAKE ENERGY TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611521651.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,该方案依赖氟化铋在首次钠化过程中的原位转化,会消耗无负极体系中有限的活性钠;同时,生成的氟化钠及粘结剂可能增加界面阻抗,普通浆料涂层在微孔集流体孔壁上的分布和附着也难以精确控制

Benefits of technology

(1)本申请制备了一种用于无负极钠金属电池的改性多孔铝箔复合集流体,包括多孔铝箔、固定于铝箔表面及孔壁的金属Bi成核层,以及由NaF和单壁碳纳米管构成的非连续人工界面层。多孔铝箔可分散局部电流并提供沉钠空间,金属Bi成核层能够降低钠成核过电位,促进均匀沉积;NaF可调控界面组成、抑制副反应,碳纳米管则构建导电网络并提高界面层稳定性。通过预先构筑Bi/NaF界面,可减少首次钠化过程中的活性钠损耗,并改善钠沉积/剥离可逆性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017990A_ABST
    Figure CN123017990A_ABST
Patent Text Reader

Abstract

The application discloses a modified porous aluminum foil composite current collector for a negative-electrode-free sodium metal battery, and belongs to the technical field of current collectors for negative-electrode-free sodium metal batteries, and comprises a porous aluminum foil, wherein a metal Bi nucleation layer and an artificial interface layer are sequentially arranged on the surface of the porous aluminum foil, and the artificial interface layer at least comprises NaF and carbon nanotubes; the porous aluminum foil is used for providing a sodium deposition space, the metal Bi nucleation layer is used for providing sodium-attracting nucleation sites, and the artificial interface layer is beneficial to maintaining electronic transmission and improving cycle interface stability; when the modified porous aluminum foil composite current collector is applied to the negative-electrode-free sodium metal battery, the battery exhibits higher first-cycle coulombic efficiency, capacity retention rate and cycle life, and lower impedance growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of current collector technology for sodium metal batteries without negative electrodes, and particularly relates to a modified porous aluminum foil composite current collector for sodium metal batteries without negative electrodes. Background Technology

[0002] Electrodeless sodium metal batteries (AFSBs) have advantages such as eliminating the need for excessive sodium storage on the negative electrode side, high energy density, simple manufacturing steps, and low cost. Compared with traditional sodium metal batteries, they can alleviate the problem of limited energy density caused by high negative electrode reactivity, positive and negative electrode capacity imbalance, and poor cycle stability. They are expected to become a potential system for large-scale energy storage and are suitable for grid-side and industrial and commercial energy storage scenarios.

[0003] However, sodium deposition / stripping during cycling can easily lead to Na+ deposition / stripping. + Uneven deposition leads to the formation of dendrites and "dead sodium," causing continuous SEI film rupture / reconstruction and resulting in sodium loss and degradation. In anode-less sodium metal batteries, lacking additional metal reserves, the irreversible sodium loss during deposition / stripping can only be absorbed from the Na₂O₃ at the cathode. + Therefore, uneven deposition is more likely to lead to rapid capacity decay and exacerbate cycle life and safety risks. Currently, the modification of current collectors in anode-free sodium metal batteries mainly focuses on reducing the sodium nucleation energy barrier, achieving uniform charge distribution, and constructing a stable SEI film. Commonly used methods include introducing sodium-loving metals or polar compounds, constructing carbon-based or three-dimensional porous frameworks, and modifying with artificial interface layers.

[0004] These strategies can improve deposition uniformity and cycle stability to some extent, but problems such as nucleation site instability, insufficient kinetics, or complex processes still exist. There is an urgent need to develop stable, sodium-loving current collectors that are easy to prepare on a large scale.

[0005] Currently, the industry is targeting Na + Solutions to improve deposition problems and battery cycle stability mainly focus on current collector modification, sodium-loving coatings, and the construction of artificial interface layers.

[0006] For example, CN121306933A discloses a coating for a negative electrode current collector in a negative electrode-free sodium metal battery and its preparation method. This involves preparing a slurry from active materials such as bismuth fluoride, conductive carbon materials, and a binder, and coating it onto the surface of copper or aluminum foil. During the initial sodium plating process, the conversion reaction of bismuth fluoride generates metallic bismuth and sodium fluoride, thereby reducing the sodium nucleation overpotential and improving interfacial stability. However, this method relies on the in-situ conversion of bismuth fluoride during the initial sodium plating process, which consumes the limited active sodium in the negative electrode-free system. Simultaneously, the generated sodium fluoride and binder may increase interfacial impedance, and the distribution and adhesion of ordinary slurry coatings on the pore walls of microporous current collectors are difficult to control precisely. Therefore, under conditions of low sodium inventory, high areal capacity, and long-term cycling, this method still has room for further optimization. Summary of the Invention

[0007] The objective of the first aspect of this application is to provide a modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery, so as to improve the reversibility of sodium deposition / stripping and the stability of the cycling interface of a high-temperature electrolyte for a negative electrode-free sodium-ion battery.

[0008] The technical solution adopted in this application is as follows: A modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery includes a porous aluminum foil, on the surface of which a metal Bi nucleation layer and an artificial interface layer are sequentially disposed, wherein the artificial interface layer includes at least NaF and carbon nanotubes.

[0009] The design concept of this application is as follows: (1) Porous aluminum foil is selected as the base layer. Porous aluminum foil is lightweight and has good conductivity. Its porous structure is conducive to dispersing local current and providing space for sodium deposition. It is also suitable for continuous processing.

[0010] (2) A metallic Bi nucleation layer is formed on the surface and pore walls of the porous aluminum foil. Metallic Bi has good sodium affinity, which can provide sodium nucleation sites, which is beneficial to reducing sodium nucleation resistance and improving sodium deposition uniformity.

[0011] (3) An artificial interface layer composed of NaF, carbon nanotubes, and PAN is formed on the surface of a porous aluminum foil with a metallic Bi nucleation layer. NaF, as a fluorine-containing inorganic component, is beneficial for regulating interfacial reactions; carbon nanotubes are used to construct an electron transport network; and PAN (polyacrylonitrile) is used as a binder to fix NaF and carbon nanotubes to the surface of the porous aluminum foil. This artificial interface layer helps maintain electron and ion transport, improves the stability of the cycling interface, and reduces interfacial side reactions and irreversible sodium loss, thereby improving the first-cycle reversibility and cycle performance of the battery.

[0012] The second objective of this application is to provide a method for preparing a modified porous aluminum foil composite current collector for use in a sodium metal battery without a negative electrode, comprising the following steps: (1) Pretreatment: Porous aluminum foil was selected as the current collector, and the porous aluminum foil was subjected to degreasing, water washing and activation treatment in sequence. (2) Electroplating: The pretreated porous aluminum foil is placed in a Bi-containing container. 3+ A roll-to-roll pulse electroplating process was performed in an acidic plating solution to obtain a porous aluminum foil current collector with a metallic Bi nucleation layer. (3) Coating: NaF, carbon nanotubes (CNTs) and binder are added to anhydrous N-methylpyrrolidone in a certain ratio and dispersed to form a composite slurry. The composite slurry is coated on the surface of the porous aluminum foil current collector with a metal Bi nucleation layer obtained in step (2), and a NaF / CNT artificial interface layer is formed on the outside of the metal Bi nucleation layer to obtain a modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery.

[0013] Further settings are as follows: In step (1): The porous aluminum foil is one of roll-to-roll punched aluminum foil or porous aluminum foil formed by etching. The thickness of the porous aluminum foil is 12-30μm, preferably 15-25μm; the pore size or equivalent pore size is 30-150μm, preferably 50-100μm; and the porosity is 10-35%, preferably 15-30%.

[0014] In step (2): The roll-to-roll pulse electroplating takes 25-70 seconds.

[0015] Metallic Bi was deposited on both sides and the pore walls of a porous aluminum foil via roll-to-roll pulse electroplating. The surface loading of the Bi nucleation layer, based on the projected area of ​​a single side of the porous aluminum foil, was 0.02-0.15 mg / cm². 2 Preferably, it is 0.03-0.08 mg / cm³. 2 .

[0016] The Bi-containing 3+ Acidic plating solution: Bi 3+ The concentration is 0.10–0.20 mol / L, the pH of the acidic plating solution is 0.3–0.6, and the temperature of the acidic plating solution is 20–35℃.

[0017] In step (3): The NaF, carbon nanotubes, and binder are formulated in the following mass percentages: NaF 30-75%, carbon nanotubes 20-65%, and binder 0.5-10%.

[0018] The carbon nanotubes are selected from one or more of single-walled carbon nanotubes (SWCNTs), double-walled carbon nanotubes (DWCNTs), multi-walled carbon nanotubes (MWCNTs), and functionalized carbon nanotubes.

[0019] The adhesive is selected from one or more of polyacrylonitrile (PAN), polyimide, polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR).

[0020] Preferably, the composite slurry is composed of NaF, single-walled carbon nanotubes and polyacrylonitrile, and the mass ratio of NaF, single-walled carbon nanotubes and polyacrylonitrile is 65:30:5.

[0021] In step (3), the coating process has a solid content of 1.0%-3.0% in the composite slurry and a coating speed of 0.4-0.6 m / min.

[0022] After the coating process in step (3), an artificial interface layer is formed on the surface of the metal Bi nucleation layer of the porous aluminum foil current collector. Based on the single-sided projected area of ​​the porous aluminum foil, the surface loading of the artificial interface layer is 0.05-0.50 mg / cm². 2 Preferably, it is 0.10-0.30 mg / cm³. 2 .

[0023] The third objective of this application is to provide an application of a modified porous aluminum foil composite current collector for use in a cathode-free sodium metal battery, in order to improve the reversibility of sodium deposition / stripping and the stability of the cycle interface, and reduce the irreversible loss of active sodium.

[0024] The sodium metal battery without a negative electrode includes a positive electrode, a negative electrode current collector, a separator, and an electrolyte. The positive electrode, negative electrode current collector, and separator are stacked or wound to form an electrode assembly, and no metallic sodium is pre-placed on the negative electrode side. During the first charge, the sodium is released from the positive electrode. + A sodium metal negative electrode is formed by in-situ deposition on the surface of the negative electrode current collector.

[0025] The negative electrode current collector is a modified porous aluminum foil composite current collector prepared as described above for use in a negative electrode-free sodium metal battery.

[0026] The positive electrode sheet comprises a positive electrode active material, a conductive agent, a binder, and a positive electrode current collector. The positive electrode active material is one or more of sodium iron pyrophosphate, sodium vanadium phosphate, sodium vanadium fluorophosphate, layered oxides, Prussian blue, Prussian white, and their analogues; the conductive agent is one or more of conductive carbon black (SP), acetylene black, carbon nanotubes, or graphene; the binder is one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, or polyacrylic acid; and the positive electrode current collector is one of aluminum foil, carbon-coated aluminum foil, or porous aluminum foil.

[0027] The electrolyte comprises a sodium salt and a solvent. The sodium salt is selected from one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium tetrafluoroborate, sodium bis(oxalate-borate), or sodium perchlorate; the solvent is selected from one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (G2), triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene carbonate, and dimethyl carbonate.

[0028] The diaphragm is selected from any one of polypropylene diaphragm (PP), polyethylene diaphragm (PE), inorganic ceramic coated diaphragm, and polypropylene / polyethylene composite ceramic diaphragm.

[0029] Compared with existing technical solutions, this application has the following advantages: (1) This application prepares a modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery, comprising a porous aluminum foil, a metal Bi nucleation layer fixed on the surface and pore walls of the aluminum foil, and a discontinuous artificial interface layer composed of NaF and single-walled carbon nanotubes. The porous aluminum foil can disperse local current and provide space for sodium deposition, the metal Bi nucleation layer can reduce the sodium nucleation overpotential and promote uniform deposition; NaF can regulate the interface composition and suppress side reactions, while carbon nanotubes construct a conductive network and improve the stability of the interface layer. By pre-constructing the Bi / NaF interface, the loss of active sodium during the initial sodium formation process can be reduced, and the reversibility of sodium deposition / stripping can be improved.

[0030] (2) The modified porous aluminum foil composite current collector prepared in this application is used in sodium metal batteries without negative electrodes, which is beneficial to improving the reversibility of sodium deposition / stripping and the stability of the cycle interface, thereby improving the first-cycle coulombic efficiency and cycle performance of the battery. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the modified porous aluminum foil composite current collector of this application.

[0032] In the figure: 1. Porous aluminum foil; 2. Pore; 3. Metallic Bi nucleation layer; 4. NaF particles; 5. Carbon nanotubes; 6. Artificial interface layer. Detailed Implementation

[0033] The technical solution of this application will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of this application and should not be construed as limiting the scope of protection of this application. Unless otherwise stated, the raw materials and reagents used in the following embodiments are commercially available products or can be prepared by known methods.

[0034] First, combined Figure 1 This application describes the structure and working mechanism of a modified porous aluminum foil composite current collector for use in a negative electrode-less sodium metal battery: like Figure 1 As shown, a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode includes a porous aluminum foil 1, on the surface of which a metal Bi nucleation layer 3 and an artificial interface layer 6 are sequentially disposed.

[0035] The porous aluminum foil 1 serves as the base layer and has multiple channels 2. Its porous structure is beneficial for dispersing local currents and providing space for sodium deposition, while also being suitable for continuous processing.

[0036] The metallic Bi nucleation layer 3 is formed on the surface and pore walls of the porous aluminum foil 1 using an electroplating process. Metallic Bi has good sodium affinity, which can provide sodium nucleation sites, thus helping to reduce sodium nucleation resistance and improve sodium deposition uniformity.

[0037] The artificial interface layer 6 includes NaF particles 4 and carbon nanotubes 5. NaF particles 4, as a fluorine-containing inorganic component, are beneficial for regulating interfacial reactions. Carbon nanotubes 5 are used to construct an electron transport network. The artificial interface layer 6 helps maintain electron and ion transport, improves the stability of the cycling interface, and reduces interfacial side reactions and irreversible sodium loss, thereby improving the first-cycle reversibility and cycle performance of the battery.

[0038] The following detailed embodiments illustrate the preparation and application of a modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery.

[0039] The "Bi-containing" mentioned in the embodiments 3+ The acidic plating solution was prepared as follows: Nitric acid was added to deionized water to prepare a nitric acid aqueous solution, then bismuth nitrate pentahydrate was added and stirred until clear to obtain a solution containing Bi. 3+ Acidic plating solution: Bi 3+ The concentration is 0.15 mol / L, the pH of the acidic plating solution is 0.4–0.5, and the temperature of the acidic plating solution is 25±2℃. During the electroplating process, the acidic plating solution is kept free of visible precipitates.

[0040] Example 1

[0041] (1) Pretreatment: A porous aluminum foil with a thickness of 20 μm, a pore size of 50 μm, and an open porosity of 20% was selected. The porous aluminum foil was subjected to alkaline degreasing, water washing, and acid pickling activation treatment in sequence, and then vacuum dried at 60-80℃ to constant weight before weighing and recording the mass before electroplating.

[0042] (2) Electroplating: The pretreated porous aluminum foil is placed in a Bi-containing container. 3+Roll-to-roll pulse electroplating is performed in an acidic plating solution to deposit metallic Bi on both sides of the porous aluminum foil or on the pore walls, resulting in a porous aluminum foil current collector with a metallic Bi nucleation layer. The roll-to-roll pulse electroplating has a peak current density of 1.0 A / dm², a duty cycle of 20%, a pulse frequency of 100 Hz, and a plating time of 43 s. After plating, the porous aluminum foil is thoroughly washed with water and then vacuum dried at 60-80°C to constant weight before being weighed and its post-plating mass is recorded.

[0043] Electroplating was used to form a metallic Bi nucleation layer on the surface and pore walls of porous aluminum foil. Based on the mass difference before and after electroplating and the double-sided projected area of ​​the porous aluminum foil, the areal loading of the metallic Bi nucleation layer was calculated to be 0.05 mg / cm². 2 (Based on the projected area of ​​a single side of the porous aluminum foil).

[0044] (3) Coating: NaF particles, single-walled carbon nanotubes (SWCNTs) and polyacrylonitrile (PAN) were mixed in a mass ratio of 65:30:5 and then added to anhydrous N-methylpyrrolidone (NMP) to disperse and form a composite slurry with a solid content of 2.0%. The composite slurry was coated on both sides of the porous aluminum foil current collector with metal Bi nucleation layer obtained in step (2) in an intermittent coating manner using an intermittent coating method at a coating speed of 0.50 m / min. After coating, the current collector was dried and leveled to obtain the modified porous aluminum foil composite current collector.

[0045] By coating a composite slurry, a NaF / CNT artificial interface layer is formed on both sides of the metal Bi nucleation layer of the porous aluminum foil current collector. The surface loading of the NaF / CNT artificial interface layer on each side is 0.20 mg / cm² (based on the single-sided projected area of ​​the porous aluminum foil).

[0046] To investigate the effects of different preparation processes on the performance of modified porous aluminum foil composite current collectors, the following examples and comparative examples were conducted.

[0047] Example 2

[0048] The preparation method is the same as in Example 1, except that the electroplating time in step (2) is adjusted to 26 s, and the surface loading of the Bi metal nucleation layer is controlled to be 0.03 mg / cm². 2 .

[0049] Example 3

[0050] The preparation method is the same as in Example 1, except that the electroplating time in step (2) is adjusted to 69 s, and the surface loading of the metal Bi nucleation layer is controlled to be 0.08 mg / cm². 2 .

[0051] Example 4

[0052] The preparation method is the same as in Example 1, except that the coating process in step (3) is adjusted, the slurry solid content is 1.0%, the coating speed is 0.5 m / min, and the surface loading of the NaF / CNT artificial interface layer is controlled to be 0.10 mg / cm. 2 .

[0053] Example 5

[0054] The preparation method is the same as in Example 1, except that the coating process in step (3) is adjusted, the slurry solid content is 3.0%, the coating speed is 0.5 m / min, and the surface loading of the NaF / CNT artificial interface layer is controlled to be 0.30 mg / cm. 2 .

[0055] Comparative Example 1 A porous aluminum foil with a thickness of 20 μm, a pore size of 50 μm, and an open area of ​​20% is used, but no electroplating or coating processes are performed.

[0056] Comparative Example 2 The preparation method is the same as in Example 1, except that only the electroplating process in step (2) is performed, but the coating process in step (3) is not performed, to obtain a porous aluminum foil current collector with a metal Bi nucleation layer. The surface loading of the metal Bi nucleation layer is 0.05 mg / cm² based on the single-sided projected area of ​​the aluminum foil. 2 .

[0057] Comparative Example 3 The preparation method is the same as in Example 1, except that only the coating process in step (3) is performed, but the electroplating process in step (2) is not performed, to obtain a porous aluminum foil current collector with a NaF / CNT artificial interface layer. The surface loading of the NaF / CNT artificial interface layer is 0.20 mg / cm² based on the single-sided projected area of ​​the aluminum foil. 2 .

[0058] Application Examples

[0059] The porous aluminum foil current collectors prepared in the aforementioned examples and comparative examples were applied to a sodium metal battery without a negative electrode, and their electrochemical performance was tested.

[0060] A sodium metal battery without a negative electrode includes a positive electrode, a negative electrode current collector, a separator, and an electrolyte.

[0061] Positive electrode sheet: Sodium iron pyrophosphate (NFPP), Super P, and PVDF were mixed in a mass ratio of 90:5:5, and N-methylpyrrolidone (NMP) was added to prepare a positive electrode slurry, which was then coated onto the surface of aluminum foil; the single-sided active material loading of the positive electrode was 10 mg / cm³. 2 After vacuum drying, cut and set aside.

[0062] Negative electrode current collector: a porous aluminum foil current collector prepared using the aforementioned examples and comparative examples.

[0063] The diaphragm is a 16μm thick polypropylene / polyethylene composite ceramic diaphragm with a single-sided ceramic coating, cut into 60 mm × 47 mm rectangles, with the ceramic coating facing the negative electrode composite current collector.

[0064] Electrolyte: NaPF6 was dissolved in diethylene glycol dimethyl ether in an argon atmosphere glove box to obtain an electrolyte with a concentration of 1 mol / L; the water and oxygen content in the glove box was less than 0.1 ppm.

[0065] Battery assembly: The negative electrode current collector was cut into a rectangle of 58 mm × 45 mm, with pre-reserved welding areas for the tabs at the edges; the NFPP positive electrode sheet was cut into a rectangle of 56 mm × 43 mm. A PP / PE composite ceramic separator with a total thickness of 16 μm was selected and cut into a rectangle of 60 mm × 47 mm. The positive electrode sheet, separator, and negative electrode current collector were stacked alternately, with 10 layers of positive electrode sheet and 11 layers of negative electrode current collector to obtain a bare cell. After welding the positive and negative electrode tabs, the bare cell was placed in an aluminum-plastic film outer packaging bag, with the bag opening kept open, and vacuum dried at 80-110℃ for 8-12 h to obtain a dry cell. Approximately 0.8-1.0 mL of electrolyte was injected into the dry cell, and after vacuum heat sealing, it was allowed to stand at room temperature for 8-12 h. Then, formation, shaping, and capacity testing were performed sequentially to obtain a sodium metal battery without a negative electrode. The rated capacity of this battery is 500 mAh.

[0066] Performance testing: First-round coulomb efficiency and post-formation capacity tests: The battery was left to stand at 25±2℃ for 12 h, then charged at a constant current of 0.05C to 3.8 V, followed by constant voltage charging until the current dropped to 0.02C. The capacity of the first charge cycle was recorded. After standing for 30 min, the battery was discharged at 0.05C to 1.5 V. The capacity of the first charge and discharge cycles was recorded, and the coulombic efficiency of the first cycle was calculated. Subsequently, two charge-discharge cycles were performed at 0.1C for formation, and the capacity of the third discharge cycle was recorded as the capacity after formation.

[0067] Cyclic performance test: After the above formation is completed, the battery is left to stand for 1 hour, then charged at a constant current of 0.5C to 3.8V, and then charged at a constant voltage until the current drops to 0.05C; after standing for 1 hour, it is discharged at a constant current of 1C to 1.5V. The above steps are repeated, and the capacity retention rate and the number of cycles when the discharge capacity decays to 80% of the initial capacity are recorded. The C-rate is calculated based on the actual capacity after formation.

[0068] Internal resistance and interface impedance testing: After battery formation and after 50 and 100 cycles, the battery was adjusted to 50% state of charge and left to rest for 1 hour. Subsequently, a 10-second discharge pulse test was performed at a 1C current, and the DC internal resistance was calculated based on the voltage change before and after the pulse. At the same time, electrochemical impedance spectroscopy (EIS) was performed, with an AC disturbance voltage amplitude of 5 mV and a frequency scan range of 100 kHz to 10 mHz. The impedance spectra and overall impedance changes of the battery at different cycling stages were compared.

[0069] The test results are shown in Table 1: Table 1 .

[0070] Note: The surface loading of the Bi nucleation layer and the NaF / CNT artificial interface layer are calculated based on the single-sided projected area of ​​the porous aluminum foil after drying.

[0071] analyze: As can be seen from the comparison of Example 1 and Comparative Examples 1-3, after simultaneously setting the metal Bi nucleation layer and the NaF / CNT artificial interface layer, the first-cycle coulombic efficiency, capacity retention and cycle life of the battery are improved, and the impedance growth is slowed down. This indicates that the modified porous aluminum foil composite current collector is beneficial to improving the reversibility of sodium deposition / stripping and the stability of the cycle interface.

[0072] A comparison of Examples 1-3 shows that both excessively low and excessively high areal loadings of the Bi metal nucleation layer are detrimental to battery performance. When the loading is too low, the number of sodium-affinity nucleation sites provided by Bi metal is limited; when the loading is too high, it may increase irreversible sodium consumption and occupy some sodium deposition space. When the areal loading of the Bi metal nucleation layer is 0.05 mg / cm³... 2 At that time, the battery's overall performance was good.

[0073] A comparison of Examples 1, 4, and 5 shows that when the areal loading of the NaF / CNT artificial interface layer is too low, its interface regulation effect is limited; when the areal loading is too high, it may increase the interface transport resistance. Under the test conditions of this application, the areal loading of the NaF / CNT artificial interface layer is 0.20 mg / cm². 2 At that time, the battery cycle stability was good.

[0074] As can be seen from the comparison of Examples 1-5 and Comparative Examples 1-3, the porous aluminum foil provides space for sodium deposition, the metallic Bi nucleation layer provides sodium-affinity nucleation sites, and the NaF / CNT artificial interface layer helps maintain electron transport and improve cycle interface stability. When all three are combined, the battery exhibits higher first-cycle coulombic efficiency, capacity retention, and cycle life, as well as lower impedance growth, indicating that the modified porous aluminum foil composite current collector prepared in this application is beneficial to improving the first-cycle reversibility and cycle stability of the anode-free sodium metal battery.

Claims

1. A modified porous aluminum foil composite current collector for use in a sodium metal battery without a negative electrode, comprising porous aluminum foil, characterized in that: A metal Bi nucleation layer and an artificial interface layer are sequentially disposed on the surface of a porous aluminum foil. The artificial interface layer includes at least NaF and carbon nanotubes.

2. A method for preparing the modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode as described in claim 1, characterized in that: Includes the following steps: (1) Pretreatment: Porous aluminum foil was selected as the current collector, and the porous aluminum foil was subjected to degreasing, water washing and activation treatment in sequence. (2) Electroplating: The pretreated porous aluminum foil is placed in a Bi-containing container. 3+ A roll-to-roll pulse electroplating process was performed in an acidic plating solution to obtain a porous aluminum foil current collector with a metallic Bi nucleation layer. (3) Coating: NaF, carbon nanotubes and binder are added to anhydrous N-methylpyrrolidone in a certain ratio and dispersed to form a composite slurry. The composite slurry is coated on the surface of the porous aluminum foil current collector with metal Bi nucleation layer obtained in step (2) and an artificial interface layer is formed on the outside of the metal Bi nucleation layer to obtain a modified porous aluminum foil composite current collector for a negative electrode-free sodium metal battery.

3. The method for preparing a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode according to claim 2, characterized in that: In step (1): the porous aluminum foil is one of roll-to-roll punched aluminum foil or porous aluminum foil formed by etching. The thickness of the porous aluminum foil is 12-30 μm, the pore size or equivalent pore size is 30-150 μm, and the porosity is 10-35%.

4. The method for preparing a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode according to claim 2, characterized in that: In step (2): the roll-to-roll pulse electroplating takes 25-70 seconds. Electroplating deposits metallic Bi on both sides and the pore walls of the porous aluminum foil, forming a metallic Bi nucleation layer. Based on the single-sided projected area of ​​the porous aluminum foil, the surface loading of the metallic Bi nucleation layer is 0.02-0.15 mg / cm². 2 .

5. The method for preparing a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode according to claim 2, characterized in that: In step (3): the NaF, carbon nanotubes and binder are mixed in the following mass percentage ratio: NaF is 30-75%, carbon nanotubes are 20-65%, and binder is 0.5-10%.

6. The method for preparing a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode according to claim 2, characterized in that: In step (3): the carbon nanotubes are selected from one or more of single-walled carbon nanotubes, double-walled carbon nanotubes, multi-walled carbon nanotubes, and functionalized carbon nanotubes.

7. The method for preparing a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode according to claim 2, characterized in that: In step (3): the adhesive is selected from one or more of polyacrylonitrile, polyimide, polyvinylidene fluoride, carboxymethyl fiber, and styrene-butadiene rubber.

8. The method for preparing a modified porous aluminum foil composite current collector for a sodium metal battery without a negative electrode according to claim 2, characterized in that: In step (3), the coating process involves a composite slurry with a solid content of 1.0%-3.0% and a coating speed of 0.4-0.6 m / min. An artificial interface layer is formed by coating the metal Bi nucleation layer on the surface of the porous aluminum foil current collector. Based on the single-sided projected area of ​​the porous aluminum foil, the surface loading of the artificial interface layer is 0.05-0.50 mg / cm². 2 .

9. The application of the modified porous aluminum foil composite current collector of claim 1 for use in the preparation of a non-negative electrode sodium metal battery.

10. The application of the modified porous aluminum foil composite current collector according to claim 9 in the preparation of a negative electrode-free sodium metal battery, characterized in that: The negative electrode-free sodium metal battery includes a positive electrode sheet, a negative electrode current collector, a separator, and an electrolyte; The negative electrode current collector is a modified porous aluminum foil composite current collector used in negative electrode-free sodium metal batteries. The positive electrode sheet comprises a positive electrode active material, a conductive agent, a binder, and a positive electrode current collector. The positive electrode active material is one or more of sodium iron pyrophosphate, sodium vanadium phosphate, sodium vanadium fluorophosphate, layered oxides, Prussian blue, Prussian white, and their analogues. The conductive agent is one or more of conductive carbon black, acetylene black, carbon nanotubes, or graphene. The binder is one or more of polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, or polyacrylic acid. The positive electrode current collector is one of aluminum foil, carbon-coated aluminum foil, or porous aluminum foil. The electrolyte comprises a sodium salt and a solvent, wherein the sodium salt is selected from one or more of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium tetrafluoroborate, sodium bis(oxalate-borate) or sodium perchlorate; and the solvent is selected from one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene carbonate, and dimethyl carbonate. The diaphragm is selected from any one of polypropylene diaphragm, polyethylene diaphragm, inorganic ceramic coated diaphragm, and polypropylene / polyethylene composite ceramic diaphragm.

Citation Information

Patent Citations

  • Negative electrode current collector coating of non-negative electrode sodium metal battery and preparation method of negative electrode current collector coating

    CN121306933A